2014
DOI: 10.3109/19396368.2014.952391
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease in subfertile men and the effect of mesalazine on fertility

Abstract: This study aimed to examine the effect of mesalazine on fertility. In this retrospective analysis of 1,225 male subfertile patients, we reviewed the cases of inflammatory bowel disease (IBD) in the medical records and evaluated the prevalence of the disease in our reproduction center. Specifically, we examined IBD patients who ceased mesalazine during male infertility treatment, and compared the seminogram of these patients before and after discontinuation of mesalazine. We also analyzed pregnancy outcome afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Six of these seven patients discontinued their mesalazine treatment. Sperm motility and total motile sperm count were significantly improved in all patients after discontinuation, and most were able to conceive successful pregnancy with their partners . Thus, in male patients on mesalazine who experience a decrease in libido, sexual dysfunction, or difficulty conceiving a pregnancy, a trial of mesalazine discontinuation is a reasonable first approach (Table ).…”
Section: Resultsmentioning
confidence: 98%
“…Six of these seven patients discontinued their mesalazine treatment. Sperm motility and total motile sperm count were significantly improved in all patients after discontinuation, and most were able to conceive successful pregnancy with their partners . Thus, in male patients on mesalazine who experience a decrease in libido, sexual dysfunction, or difficulty conceiving a pregnancy, a trial of mesalazine discontinuation is a reasonable first approach (Table ).…”
Section: Resultsmentioning
confidence: 98%
“…The negative effect of mesalazine on fertility has been shown in patients with irritable bowel disease that at a certain point requires treatment cessation to achieve fertility. Indeed, the mean sperm concentration, sperm motility, percentage of spermatozoa with normal form, seminal fluid volume, and total motile sperm count increase after mesalazine discontinuation [42]. Another study showed a decrease of sperm count and motility in mice treated with sulfasalazine [43].…”
Section: Anti-inflammatory Treatmentmentioning
confidence: 99%
“…This improvement resulted in four of the six patients achieving pregnancy. The authors concluded that mesalazine cessation should only be pursued in patients with stable IBD …”
Section: Resultsmentioning
confidence: 99%